“Caracterización de las rocas zeolíticas en la parroquia de Catacocha cantón Paltas de la provincia de Loja, con fines aprovechables”. - Sánchez Carrillo, Sandro Daniel (2021)
The present investigation called "Characterization of Zeolitic Rocks of the Catacocha Parish, Paltas Canton of the Loja Province, for exploitable purposes", proposes in its development the power to determine zeolitic minerals in tubaceous rocks, in order to be industrially exploited. Thus, the study is made up of several stages, starting from the collection and preparation of base information, for later realization of a field stage that primarily allows the collection of rock samples, based on a previous geological analysis, implemented charts geological, aerial photographs and related studies in the advocacy sector. The collected samples were selected under various parameters, for the development of the respective analyzes, starting with the x-ray fluorescence analysis that leads to determine the chemical composition of each sample, then through a second selection the mineralogical analysis was developed to the best prospects implementing x-ray diffraction analysis. With the developed analyzes, it was possible to determine the presence of important zeolitic mineralogical phases such as clinoptilolite, heulandite and mordenite in amounts greater than 50%, which leads to the denomination of the analyzed rocks as zeolitic rocks. Finally, the data obtained was analyzed and related to data from established deposits of zeolitic rocks, taking into account the origin of the deposits, the rock that houses the mineral, the chemical composition of the rock and the concentration of the mineral present, with which A possible overview of the application of the determined zeolitic rocks and their potential industrial use is given. Keywords: Minerals, rock samples, analysis, zeolitic rocks, x-ray fluorescence, x-ray diffraction,